2018
DOI: 10.1590/s0100-204x2018000300006
|View full text |Cite
|
Sign up to set email alerts
|

Growth and quality of potted ornamental peppers treated with paclobutrazol

Abstract: The objective of this work was to evaluate the action of paclobutrazol (PBZ) on the growth and ornamental value of two pepper accessions and two commercial cultivars of ornamental pepper - Biquinho Vermelha and Bode Amarela. A PBZ aqueous solution (250 mL) was used to soak the substrate at 0, 20, 40, and 60 mg L-1 a.i. concentrations when the plants had 12 cm height. At the end of plant growth, the follwoing parameters were evaluated: plant height, chlorophyll content in leaves, number of fruit and leaves, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…The results showed that PP333 significantly ameliorated the adverse effects of NaCl stress in Vigna unguiculata plants (Manivannan et al 2007). Leaf or substrate spraying can effectively reduce plant height and the MDA content, increase the thickness of the main stem, and increase the leaf Chl content and soluble sugar content (Tekalign et al 2004, França et al 2018, Liu et al 2020.…”
Section: Introductionmentioning
confidence: 96%
“…The results showed that PP333 significantly ameliorated the adverse effects of NaCl stress in Vigna unguiculata plants (Manivannan et al 2007). Leaf or substrate spraying can effectively reduce plant height and the MDA content, increase the thickness of the main stem, and increase the leaf Chl content and soluble sugar content (Tekalign et al 2004, França et al 2018, Liu et al 2020.…”
Section: Introductionmentioning
confidence: 96%
“…This divergence of results can be explained by the fact that the effects caused by PBZ on plants vary between species, varieties, concentration and form of application (Rademacher, 2000). França et al (2018) and Ribeiro et al (2019b) studying the effect of PBZ on Capsicum, obtained different responses among the varieties studied, when using different ways of treatment, concentrations and varieties of pepper. Regarding the abscission of fruits, the cultivars were divided into two distinct groups, when treated with 5, 10 or 20 mg L -1 PBZ (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The growth regulator, paclobutrazol (PBZ) was applied after the plants had a height between 10 and 15 cm. Each pot received 150 mL of the PBZ solution drenched directly in the substrate at concentrations of 0.5, 10 and 20 mg L -1 , corresponding to 0.75, 1.5 and 3 mg of the active principle (250 g ai PBZ per liter, Syngenta Crop Protection), similar to that described by França et al, (2018).…”
Section: Conducting the Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Se ha empleado para la manipulación química del crecimiento y desarrollo de las plantas a través de la alteración en los procesos bioquímicos y fisiológicos (Gollagi et al, 2019;Ribeiro et al, 2019), mismos que les brindan a las plantas mayor tolerancia al estrés abiótico, incremento del rendimiento y mejor rasgo fisiológico (Tesfahun, 2018). Los rasgos fisiológicos reportados son mayor contenido de clorofila, modificaciones morfológicas de las hojas (hojas más gruesas, menor área foliar, poros estomáticos más pequeños) y mayor densidad de raíces (Campos et al, 2014;França et al, 2018;Gollagi et al, 2019).…”
Section: Introductionunclassified